An Experimental Investigation and Aspen HYSYS Simulation of Waste Polystyrene Catalytic Cracking Process for the Gasoline Fuel Production - Thambiyapillai, Selvaganapathy; Ramanujam, Muthuvelayudham (Center of Biomass & Renewable Energy, Diponegoro University, 2021)
Plastic wastes are necessary to recycle due to their disposal issues around the world. They can be recycled through various techniques i.e., mechanical reprocessing, mechanical recycling, chemical recycling and incineration. Most recycling techniques are expensive and end up in producing low-grade products excluding chemical recycling; it is an eco-friendly way to deal with plastic waste. Catalytic cracking is one of the chemical recycling methods, for converting waste plastics into liquid fuel same as commercial fuels. An experimental investigation of polystyrene catalytic cracking process was conducted with impregnated fly ash catalyst and 88.4% of liquid product yield was found as a maximum at optimum operating conditions 425 ÌŠC and 60 min. The liquid fuel quality was analyzed using FTIR spectra analysis, GC/MS analysis and Physico-chemical property analysis. The GC/MS analysis shows that the fly ash cracking of polystyrene leads to the production of gasoline fuels within the hydrocarbon range of C3-C24, and the aliphatic and aromatic functional compounds were detected using FTIR analysis. Moreover, the Aspen Hysys simulation of polystyrene catalytic cracking was conducted in a pyrolytic reactor at 425 ÌŠC and at the end of the simulation, 93.6% of liquid fuel yield was predicted. It was inferred that the simulation model for the catalytic cracking is substantial to fit the experimental data in terms of liquid fuel conversion